Effects of a 10-week in-season eccentric-overload training program on muscle-injury prevention and performance in junior elite soccer players - de Hoyo, M.; Pozzo, M.; Sanudo, B.; Carrasco, L.; Gonzalo-Skok, O.; Dominguez-Cobo, S.; Moran-Camacho, E. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To analyze the effect of an eccentric-overload training program (ie, half-squat and leg-curl exercises using flywheel ergometers) with individualized load on muscle-injury incidence and severity and performance in junior elite soccer players. Methods: Thirty-six young players (U-17 to U-19) were recruited and assigned to an experimental (EXP) or control group (CON). The training program consisted of 1 or 2 sessions/wk (3-6 sets with 6 repetitions) during 10 wk. The outcome measured included muscle injury (incidence per 1000 h of exposure and injury severity) and performance tests (countermovement jump [CMJ], 10-m and 20-m sprint test). Results: Between-groups results showed a likely (ES: 0.94) lower number of days of absence per injury and a possible decrement of incidence per 1000 h of match play in EXP than in CON. Regarding muscle performance, a substantial better improvement (likely to very likely) was found in 20-m sprint time (ES: 0.37), 10-m flying-sprint time (ES: 0.77), and CMJ (ES: 0.79) for EXP than for CON. Within-group analysis showed an unclear effect in each variable in CON. Conversely, substantial improvements were obtained in CMJ (ES: 0.58), 20-m sprint time (ES: 0.32), 10-m flying-sprint time (ES: 0.95), and injury severity (ES: 0.59) in EXP. Furthermore, a possible decrement in total injury incidence was also reported in EXP. Conclusions: The eccentric-based program led to a reduction in muscle-injury incidence and severity and showed improvements in common soccer tasks such as jumping ability and linear-sprinting speed.